2014
DOI: 10.1093/toxsci/kfu258
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Embryopathy: Nitric Oxide Rescues Teratogenic Effects of Cadmium

Abstract: Although Cadmium (Cd) is a well-known heavy metal pollutant and teratogen, the mechanism behind Cd-mediated teratogenicity remains unknown. Previously, we have reported of the protective role of Nitric oxide (NO), a key signaling molecule in the embryonic developmental process, against Thalidomide-induced teratogenicity. The objective of this study was to obtain a mechanistic in-sight of the antiteratogenic potential of NO against Cd-mediated teratogenicity. To achieve this goal, we first studied the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…While Antonova et al [44] reported that preconditioning with low doses of a NO donor could accelerate the repair and maintenance of endothelial integrity via the sGC pathway. Previous reports from our lab group have also shown that treatment with NO donors or cGMP analogs can restore and protect endothelial function, morphology and barrier integrity [26,27,[45][46][47]. Similarly, we noted that addition of NO donor SP or activators of NO/sGC/cGMP activity such as YC-1 (an NO independent activator of sGC), SC (which increases cellular cGMP by PDE inhibition) and 8-Br (cGMP analogue) could blunt sFRP4 mediated effects.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While Antonova et al [44] reported that preconditioning with low doses of a NO donor could accelerate the repair and maintenance of endothelial integrity via the sGC pathway. Previous reports from our lab group have also shown that treatment with NO donors or cGMP analogs can restore and protect endothelial function, morphology and barrier integrity [26,27,[45][46][47]. Similarly, we noted that addition of NO donor SP or activators of NO/sGC/cGMP activity such as YC-1 (an NO independent activator of sGC), SC (which increases cellular cGMP by PDE inhibition) and 8-Br (cGMP analogue) could blunt sFRP4 mediated effects.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, we noted that addition of NO donor SP or activators of NO/sGC/cGMP activity such as YC-1 (an NO independent activator of sGC), SC (which increases cellular cGMP by PDE inhibition) and 8-Br (cGMP analogue) could blunt sFRP4 mediated effects. Previously we have shown that endothelial dysfunction, whether hypoxia-driven or induced by teratogens (cadmium, thalidomide), occurs primarily as a consequence of decreased intercellular NO bioavailability and/or bioactivity and elevated ROS levels, which promotes apoptosis [26,27,[45][46][47]. Superoxide production in EC has been reported to contribute to enhanced permeability of EC membrane [48], particularly as NO is known for its strong affinity to react with superoxide radicals [49] to form peroxynitirite and thereby causing leakiness of the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…The most plausible explanations point to an increased ROS production and, therefore, increased oxidative stress, increased superoxide and lipid peroxidation and cadmium‐induced lung inflammation (Cormet‐Boyaka et al, ; Song et al, ; Veeriah et al, ). This is underlined by the anti‐teratogenic potential of nitric oxide, glycine as well as zinc against Cd‐mediated teratogenicity (Daston, ; Paniagua‐Castro et al, ; Veeriah et al, ). Furthermore, Cd 2+ displays an inhibitory effect on the placental and fetal uptake of Zn 2+ and Cu 2+ (Holt and Webb, ).…”
Section: Lung Morphological Developmentmentioning
confidence: 99%
“…Occupational exposure to this metal creates also the risk of respiratory system damage (Moitra and others ; Brüning and others ) and may lead to cognitive impairment (Draz and others ; Brüning and others ). Moreover, Cd is a teratogenic and carcinogenic agent (Veeriah and others ; van Maele‐Fabry and others ). It has been recognized that exposure of the general population to this heavy metal in industrialized countries will show an increasing trend in future decades (Järup and Akesson ; Nawrot and others ).…”
Section: The Possibility Of Using a Melanocarpa Berries And Their Prmentioning
confidence: 99%